2012
DOI: 10.1007/s12039-011-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

Controlled free radical polymerization of vinyl acetate with cobalt acetoacetonate

Abstract: The polymerization of vinyl acetate with the complex catalyst of cobalt acetoacetonate [Co (acac) 2 ] and DMF ligand with benzoyl peroxide initiator has been successfully carried out in bulk and in solution. The bulk polymerization has been used in a new route consisting of a one-step polymer formation in a fine capillary tube. In this process, the high rate of propagation was used to carry out the reaction in a microcapillary tube. Under 60 • C, the colour-free reaction without solid catalyst impurity was 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 10 publications
(23 reference statements)
0
24
0
Order By: Relevance
“…3.6 at −59°C [6,10]. PVAc and PSt segments exhibited T g values of 40 and 105°C [9,12,13], respectively for the The linear fit indicated that the concentration of propagating radical species is constant and radical termination reactions are not significant over time scale of the reaction. It was found that the molecular weights increase almost linearly with conversion, indicating that the number of chains was constant and the chain transfer reactions were rather negligible [16][17][18].…”
Section: Characterization Of Pvacmentioning
confidence: 92%
See 4 more Smart Citations
“…3.6 at −59°C [6,10]. PVAc and PSt segments exhibited T g values of 40 and 105°C [9,12,13], respectively for the The linear fit indicated that the concentration of propagating radical species is constant and radical termination reactions are not significant over time scale of the reaction. It was found that the molecular weights increase almost linearly with conversion, indicating that the number of chains was constant and the chain transfer reactions were rather negligible [16][17][18].…”
Section: Characterization Of Pvacmentioning
confidence: 92%
“…3.8 (Table 3.3). The growing peak of block copolymers remained monomodal throughout the reaction, indicating that all the unreacted attachable initiators have been removed prior to polymerization [9,13,[19][20][21]. Fig.…”
Section: Characterization Of Pstmentioning
confidence: 93%
See 3 more Smart Citations